Digitalization and analytics for smart plant performance theory and applications - Zhu, Frank 1957- (Wiley-AIChE, 2021)
Front Matter -- CHALLENGES AND OPPORTUNITIES FOR DIGITALIZATION. CHALLENGES AND OPPORTUNITIES FOR DIGITALIZATION -- CHALLENGES FOR OPERATION EXCELLENCE -- MISSION OF CONNECTED PLANT -- DATA ANALYTICS FOR OPERATION EXCELLENCE -- MODEL THINKING FOR SMART OPERATIONS. MODEL THINKING FOR SMART OPERATIONS -- STATISTICS BASICS -- ADVANCED STATISTIC MODELING -- RIGOROUS PROCESS MODELING -- LINEAR OPTIMIZATION MODELING -- NONLINEAR OPTIMIZATION MODELING -- PROCESS CONTROL AND APC MODELING -- AI AND MACHINE LEARNING MODELING / Amit Gupta, Frank (Xin X) Zhu -- CONNECTED PLANT FOR SMART OPERATIONS. CONNECTED PLANT FOR SMART OPERATIONS -- CONNECTED METERING AND MEASUREMENTS / Martin Bragg -- CONNECTED ASSET AND SAFETY MANAGEMENT / Frank (Xin X) Zhu, Tony Downes -- INTEGRATED PRODUCTION PLANNING AND PROCESS CONTROL -- DIGITALIZING THE ENERGY MANAGEMENT -- INTEGRATING THE WORKFLOWS / Frank (Xin X) Zhu, Joe Ritchie -- DIGITALIZING THE WORKFORCE / Rohan McAdam -- DIGITAL SOLUTIONS FOR SMART OPERATIONS. DIGITAL SOLUTIONS FOR SMART OPERATIONS -- HONEYWELL FORGE / Matt Burd, Frank (Xin X) Zhu -- DIGITAL REEDINESS ASSESSMENT AND SIX-STEP DIGITALIZATION JOURNEY -- DIGITAL PROJECT EVALUATION AND DEVELOPMENT -- APPLICATION CASE STUDIES.